Reconstruction of the human nipple–areolar complex: a tissue engineering approach - Maistriaux, Louis; Foulon, Vincent; Fievé, Lies; Xhema, Daela; Evrard, Robin; Manon, Julie; Coyette, Maude; Bouzin, Caroline; Poumay, Yves; Gianello, Pierre; Behets, Catherine; Lengelé, Benoît (Frontiers in Bioengineering and Biotechnology, 2024)
Nipple-areolar complex (NAC) reconstruction after breast cancer surgery is challenging and does not always provide optimal long-term aesthetic results. Generating a NAC using tissue engineering techniques, as decellularization-recellularization process, is therefore an alternative option to recreate a specific 3D-NAC morphological unit, then covered with an in vitro regenerated epidermis and thereafter skin-grafted on the reconstructed breast.Human NACs were harvested from cadaveric donors and decellularized with sequential detergent baths. Cellular clearance and extracellular matrix (ECM) preservation were analyzed by histology as well as by DNA, ECM proteins, growth factors and residual SDS quantification. In vivo biocompatibility was evaluated 30 days after subcutaneous implantation of native and decellularized human NACs in rats. In vitro scaffold cytocompatibility was assessed by static seeding of human fibroblasts on their hypodermal side for 7 days while human keratinocytes were seeded on the scaffold epidermal side for 10 days by using the Reconstructed Human Epidermis technique to investigate the regeneration of a new epidermis.Decellularized NAC showed a preserved 3D morphology and appeared white. After decellularization, a DNA reduction of 98.3%, the absence of nuclear and HLA stainings at the histology confirmed the complete cellular clearance. ECM architecture and main ECM proteins were preserved, associated with the detection, and decrease of growth factors while a very low amount of residual SDS were detected after decellularization. Decellularized scaffolds were in vivo biocompatible, fully revascularized and do not induce the production of rat anti-human antibodies after 30 days of subcutaneous implantation. Scaffold in vitro cytocompatibility were confirmed by the increasing proliferation of seeded human fibroblasts during 7 days of culture, associated with a high number of living cells and a similar viability in comparison to the control cells after 7 days of static culture. Moreover, RHE technique allowed to recreate a keratinized pluristratified epithelium after 10 days of culture.Tissue engineering allowed to create acellular and biocompatible NAC with a preserved morphology, micro-architecture and matrix proteins while maintaining their cell growth potential and ability to regenerate skin epidermis. Tissue engineering could thus provide a novel alternative to a personalized and natural NAC reconstruction.